Philosophical and Anthropological Analysis of the Semiotics of the Economic and Legal System - Shcherbai, Ivanna; Slyvka, Stepan; Chornobai, Olena; Kolych, Olha; Levytska, Oksana (Տիգրան Մեծ)
The primary research method is to carry out a philosophical and anthropological analysis of the semiotics of the economic and legal system in the society of that culture. The methodology includes several theoretical methods of analysis. The economic and legal system is integral to modern social and cultural life. Its influence on forming a person‟s economic and legal culture is significantly enhanced in the era of information technology and the anthropotechnics inherent in them. All this actualises the consideration of the semiotics of the economic and legal system in the philosophical and anthropological plane and allows expanding the horizons of comprehending the cultural dimension of money, and law as semiotic phenomena, identifying the ideological, cultural, social and mythical basis on which they rely. Based on the philosophical and anthropological analysis results, the critical characterising elements of the economic and legal system in the culture and society were identified.
Keywords: Philosophy of economics